Reflecting on 12 years of training medical students in rural longitudinal integrated clerkships - Francois Coetzee; Ian Couper (AOSIS, 2024)
Longitudinal integrated clerkships (LICs) are effective in promoting careers in rural primary health care environments. This model of training medical professionals involves longer clinical placements of medical students and a different approach to learning which better prepares them for primary health care practice. Stellenbosch University created a LIC in 2011 for this purpose and has trained almost 100 doctors in their yearlong LIC since then. The past 12 years have brought about a lot of learning as this model of training was implemented, developed, and refined to suit the needs of students and the clinical environments. Contribution: Countries across the globe face challenges in recruiting and retaining doctors in rural primary health care environments. Longitudinal integrated clerkships have several educational benefits in addition to increase recruitment and retention of rural doctors, and 12 years of experience have led to a greater understanding regarding implementation and outcomes of an LIC in the South African context.